(untitled) (Global Journal of Science Frontier Research, 2022)
Knowing that the Pell and Jacobsthal sequences are second-order linear recursive sequences and that they have similarities between them this study aims to explore these sequences Thus an investigation will be carried out on the Pell and Jacobsthal numbers based on the hybrid numbers and their quaternions In this way it will be presented as a great among these hybrid themes of Pell and will be presented as a formula of hybrids of Pell Jacobsthal and will be presented transforming function and its extension to the indices